2020
DOI: 10.1016/j.advms.2019.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The clinical applications of a multigene liquid biopsy (NETest) in neuroendocrine tumors

Abstract: Purpose There are few effective biomarkers for neuroendocrine tumors. Precision oncology strategies have provided liquid biopsies for real-time and tailored decision-making. This has led to the development of the first neuroendocrine tumor liquid biopsy (the NETest). The NETest represents a transcriptomic signature of neuroendocrine tumor (NETs) that captures tumor biology and disease activity. The data have direct clinical application in terms of identifying residual disease, disease progress and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 101 publications
1
45
0
4
Order By: Relevance
“…Overall, s-CgA as a single plasma biomarker is inadequate to predict tumour progression and must be used in association with imaging followup. The role of emerging biomarker panels such as the NETest TM , has to be determined [11]. Depending on the primary tumour and symptoms of the patient, measurement of specific markers, such as gastrin, insulin, c-peptide, pro-insulin, glucagon, VIP, somatostatin, ACTH or calcitonin should be performed.…”
Section: Biochemical Markersmentioning
confidence: 99%
“…Overall, s-CgA as a single plasma biomarker is inadequate to predict tumour progression and must be used in association with imaging followup. The role of emerging biomarker panels such as the NETest TM , has to be determined [11]. Depending on the primary tumour and symptoms of the patient, measurement of specific markers, such as gastrin, insulin, c-peptide, pro-insulin, glucagon, VIP, somatostatin, ACTH or calcitonin should be performed.…”
Section: Biochemical Markersmentioning
confidence: 99%
“…Minimally invasive liquid biopsy tests for advanced cancers using blood/plasma have been shown to detect tumor-specific mutations in circulating cell-free tumor DNA (ctDNA), and recent data from studies of the NETest have shown successful detection of tumor-specific transcripts in circulating RNA ( 73 , 74 ). Genç et al.…”
Section: Molecular Mechanisms and Prognosis In Pnetsmentioning
confidence: 99%
“…There are multiple studies investigating the role of sev-eral biomarkers as well as of genetic and epigenetic alterations, including circulating tumour cells (CTCs), circulating tumour DNA (ctDNA), histone modifications and miRNAs, as prognostic factors and predictors of response to treatment [71,72]. A recently developed multigene liquid biopsy (NETest), that is based on transcriptomic evaluation of NENs, has been shown to have numerous clinical applications as it may assess the successful surgical removal of a NEN or predict the aggressive tumour behaviour and the efficacy of SSAs and PRRT [73].…”
Section: Future Perspectivesmentioning
confidence: 99%